Standard handbook of environmental engineering (New York, 1989)
The book is an comprehensive manual on the principle and practice of environmental engineering. It provides on the most significant technical aspects of air quality control, water supply, wastewater disposal, and solid waste management. It also provodes stormwater and hazardous waste management. Additional chapters provide insight into historic and fundamental aspects of legislation, quality standards, and environmental assessment procedures, which broadly define objectives of environmetal engineering services
Keywords: environmental engineering